The Ways of Making the Student’s Authentic Experience Meaningful in the Process of Primary Education - Povilaitytė, Jovita; Lenkauskaite, Jurgita (Jaunųjų mokslininkų darbai, 2020)
Recently, with an increasing focus on child-centered education, strategies to make the child’s experience meaningful in the educational process are being sought. One of the educational strategies, that highlights the importance of the child’s experience best, is experiential learning. The experiential education strategy emphasizes learning, through the ctivities that develop each child academically, physically, culturally and spiritually in the educational institution and community, supports him or her, giving the child the opportunity to benefit from his or her experience (Luckner, Nadler, 1997; Braslauskienė, Norvilienė, Šmitienė, Vismantienė, 2018). Foreign and Lithuanian authors have been increasingly theoretically substantiating the importance of students’ authentic experience in the educational process. However, there is a lack of research that reveals the ways in which the student’s authentic experience can be made meaningful already in the process of primary education, when the foundations of learning that remain relevant throughout life are laid. Therefore, the aim of the present research is to reveal the ways in which the student’s authentic experience can be made meaningful in the process of primary education. In order to achieve the research aim a written survey was conducted, in which the teachers and the head of the institution, where the principles of experiential learning where actively applied the in the process of primary education, participated (6 informants in total). Qualitative content analysis was chosen for research data analysis. The analysis of data obtained in this empirical research revealed that in the educational institution, where the research was conducted, much attention is paid to the student’s authentic experience. In order to make students’ experience meaningful in primary education, various learning methods, that help to identify the experience the students already have and develop it, were used,. According to the teachers, the process of making the students’ experience meaningful is especially evident in the activities of the day allocated for stimulation and experience. On this day, students examine, experiment, apply the knowledge they have and acquire in practice and go on trips, during which they consolidate the acquired knowledge. It was revealed that in order to give meaning to the experience the student has, it is important for the student to be active in both the activities initiated by teachers and in children’s contribution to the organization of the educational process.